“El que quiere leer que lea”. La revista Pucará (1985-1991) - Pablo Turnes (Caravelle, 2021)
In 1985 during the period called “democratic transition”, in the Argentinian province of Tucumán begins the publishing of a comic book called Pucará. Pucará adopted then a specific position to justify its inscription in the history of Argentinian comics, read and reinterpreted in a nationalistic and military key. This paper aims to replace it in its context and to tackle the concept of “tradition” of the so called “national comics”.